Marcadores moleculares para caracterização genética e genômica em espécies de Psidium - Sousa, Luara Lopes (2019)
Molecular marker can be a visible character or molecular phenotype from a specific segment of DNA, which may or may not be expressed. The DNA markers microsatellites and SNPs are the most used nowadays, allowing different studies of plant species due to their advantages such as polymorphism, abundance and robustness. Many of these are conserved and can be studied in species related to the one for which it was developed. These markers are important in the study of little known groups, such as the species of the genus Psidium L., which have an important ecological role and are of great economic interest, among them guava (Psidium guajava). In this work we aimed to develop two panels of molecular markers, one of SSR and another of SNPs, which are polymorphic and present in conserved regions for Psidium species. A multiplex panel, for interspecific characterization of 26 species of the genus, was assembled by conserved and polymorphic microsatellite markers. The 15 SSRs selected were labeled with fluorophores, tested in combinations and genotyped by capillary electrophoresis, while the SNPs markers were sequenced by the DArTseq method. For both markers, descriptive analyzes and clusters were performed, being a heatmap and dendogram for the microsatellites and a main coordinate analysis (PCoA) for the SNPs. Selected microsatellite markers and SNPs presented diversity indexes useful for studies in P. guajava. A multiplex panel containing seven microsatellite markers was established for efficient genotyping in guava genotypes. A total of 5,951 polymorphic SNPs in conserved sequences were selected to compose the chip panel for Psidium species. In general, both methodologies were efficient and both markers informative and useful for intra and interspecific studies.